Engineering psychology and cognitive ergonomics : mental workload, human physiology, and human energy : 17th International Conference, EPCE 2020, held as Part of the 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings.: mental workload, human physiology, and human energy : 17th International Conference, EPCE 2020, held as Part of the 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings. Part I (2020) - Unknown
No abstract available